Hunting and power : class, race and privilege in the Eastern Cape and the Transvaal Lowveld, c. 1880-1905 - Gess, David Wolfgang (Stellenbosch : Stellenbosch University, 2014)
Thesis (MA)--Stellenbosch University, 2014.